Intervention of a Non-Governmental Organisation and Its Implications for the Education of Slum Children - Gupta, Raj; Gangwar, Sumit (JOURNAL OF INDIAN EDUCATION, 2026)
In this Study, the researcher attempted to find out the educational interventions of NGOs in slum areas in Lucknow city. Along with interventions, the researcher also examines the enrollment of students in schools run by NGOs, significant challenges affecting the education of slum children, and strategies to overcome them. To achieve the mentioned objectives, this study employed a Cross-Sectional Survey Research Design under Descriptive Survey Research Method to examine the NGOs in India focused on marginalised children education in Lucknow. It integrated qualitative and quantitative data triangulation using content analysis and open-ended interviews, revealing insights and classifying them into themes to find NGO practices and challenges in addressing educational disparities. The findings indicate that children residing in slum areas face substantial physical, economic, and social challenges that hinder their educational progress and overall well-being. Many of these children require comprehensive support to address academic and personal development needs. Various non-governmental Organisations (NGOs) actively assist these children, focusing on educational enhancement and character building. As a result of these interventions, children are improving their overall personality development. Despite these NGOs’ various obstacles, they identify and implement effective strategies to overcome these challenges and support the children’s development. This study provides valuable insights for education stakeholders, particularly educators, by promoting inclusive practices within the classroom. It identifies various strategies that can be employed to address the diverse challenges encountered by teachers when implementing inclusive educational principles.